Optimalisasi Sistem Agribisnis Kopi Garut - Ahmad Choibar Tridakusumah; Dika Supyandi; Mahra Arari Heryanto; Adi Nugraha; Dede Abdul Hasyir Hasyir (Asosiasi Dosen Akuntansi Indonesia, 2022)
The coffee commodity planted by KTH LMDH Kramatjaya member farmers in Garut Regency has good quality, supported by representative coffee processing production facilities but has not been utilized optimally. Therefore it is necessary to carry out Pengabdian Kepada Masyarakat (PKM) regarding the optimization of the coffee agribusiness system. . The PKM method uses the Participatory Rural Appraisal (PRA) approach and the applied Good Agricultural Practices (GAP) at the production and processing stages. PKM results show that the production has not yet reached the optimal level of productivity. The post-harvest treatment of coffee harvest processing has not applied the GAP principle. The PKM activity that has been implemented is online training as an effort to increase access and demand for coffee. In addition, activities are being carried out to design portable drying beds. The next PKM activity plan includes training and mentoring related to online marketing strategies and training on the use of portable drying beds.